The investigation of usability of late cretaceous aged basalts near Dedeyolu village (Sivrice-Elazig) as crushed stone - Gurocak, Zulfu (Pamukkale Univ, 2016)
In this study, chemical and geomechanical properties of basalts of Late Cretaceous aged Elazig Magmatits were examined and the usability of basalts as crushed stone was investigated. Research was carried out in two stages including field and laboratory studies. During the field studies, weathering degree of basalts, joint spacing and RQD values were determined and blocks of basalt samples were collected from 7 different locations. Laboratory tests were carried out in accordance with the ISRM, ASTM, BS, CA and TS standards to determine physical, chemical and mechanics properties of basalts. Usability of basalts as concrete aggregate, gravel, ballast, support material and armourstone were examined using results obtained from laboratory tests and field investigations. Laboratory test results show that basalts can be used as concrete aggregate, gravel, balast and support material. However, the basalts are slow reactive characteristic and low alkalinity cement and pozzolanic additives should be used in concrete production to prevent alkali- silica reaction. The basalts do not have suitable properties for use as armourstone since spacing of joints are closed.
Keywords: Armourstone; Ballast; Crushed stone; Elazig Magmatits; Gravel